PERIBAHASA DAYAK KENINJAL: KAJIAN SEMANTIK - Idayani, Theresia; Hanye, Paternus; Patriantoro, Patriantoro (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractProverb research aims to inventory, classifying the type, form, function and meaning using the study of semantics. This research is the study of Linguistics or linguistic. The results of this research can contribute and are expected to add insight in linguistic contexts. The study of proverbs is a semantic study Keninjal Dayak in methods of descriptive and qualitative form. The approach used in this study is the semantic approach. The source of the data in this study are the Dayak languages Keninjal. The technique of determining the source of the data used is the purposive sampling. The data in the study totaled 165 proverb research data collection technique is the technique of fishing rods, interview techniques, recording Techniques. Types Ferox Keninjal Proverb is the adage, parable, perbilangan, slogan, thimble and expression. Types Ferox Keninjal proverb of the most prominent is the parable. Dayak proverb Keninjal shaped phrases divided into phrases endosentris, eksosentrik phrase, noun phrases, verbal phrases, phrases, idiomatic phrase phrase adjektifa konotatif. There is also a proverb shaped sentences consist of complete sentences, elliptical sentences sentences sideline, and minor sentences. The function of proverbs Keninjal Dayak is to advise, quips, rebuke and to declare certain circumstances. The meaning of the proverb Dayak Keninjal consists of grammatical meaning, in denotative, konotatif, conceptual, idiomatic full, partial and idiomatic meanings of proverbs. Keywords: Proverbs, Inventory, Type, Form, Function, Meaning